MATHEMATICAL MODELS OF EMERGENCIES IN OPERATING SYSTEMS TROPOSPHERIC COMMUNICATIONS - S. N. Kasanin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Mathematical models of emergency in the operation of specialpurpose computer simulators tropospheric system have been suggested.